XXIII Symposium on Hydroacoustics - Krynica Morska, May 23-26, 2006 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 2006)
The Symposia on Hydroacoustics already have their own history. The last one was held in Krynica Morska, May 23-26, 2006. Krynica Morska is an attractive seaside resort, located on the sandy strip of the Vistula Bay, separating the waters of the Vistula Lagoon from the Bay of Gdańsk.The Symposium traditionally was organized jointly by Gdańsk University of Technology and Naval University in Gdynia. Lech Kilian was the chairman of the Organizing Committee and Roman Salamon was the chairman of the Scientific Committee.XXIII Symposium on Hydroacoustics was organized under the auspieces of the Acoustic Committee of the Polish Academy of Sciences and the Polish Acoustical Society.The main symposium topics were:sound propagation in the sea,ambient and ship noise,nonlinear hydroacoustics,ultrasonic transducers,sonar systems,other topics related to underwater acoustics,environment.